TERAPI KELOMPOK REMAJA PUTRI SMK TERKAIT PERILAKU PENCEGAHAN STUNTING - Hardiyanti, Siti; Iswati, Iswati; Wijaya, Hermanto (PPM STIKES Adi Husada, 2025)
Introduction & Aim: Stunting is still one of the causes of death and has a significant impact on the growth and development of toddlers. So prevention needs to be done starting from preconception even from adolescent girls. This study shows that education related to stunting prevention behavior can be provided since adolescence, so that the incidence of stunting can be prevented early. Method of Activity: This community service uses the PIE (Planning, Intervention and Evaluation) approach which is carried out in Depok. Activities were carried out for 6 weeks which included, assessment (surveys and interviews), and implementation of interventions related to stunting prevention behavior with balanced nutrition education and physical exercise of dysmenorrhea. Results: Stunting prevention behavior in adolescents increased before and after the activity with high knowledge 88.8%, positive attitude 81.5% and good skills 44.4% Discussion: The health promotion program designed should focus on educational interventions involving games and group discussions, so as to encourage active participation and increase understanding of the importance of stunting prevention behaviors.